Kemampuan Menyimak melalui Film “ Nicos Weg A1” dalam Pembelajaran Bahasa Jerman - Hilda Purnama Januarti; Syamsu Rijal (Phonologie : Journal of Language and Literature, 2022)
Abstract. This study aims to determine the improvement in listening comprehension of X SMA Negeri 2 students through film media. The type of research used is Classroom Action Research's Kemmis and Me Taggart models. The subjects in this study were Class X MIPA 5 students, a total of 36 people. This research was conducted in two cycles, namely Cycle I and Cycle II, and each cycle consisted of four phases, namely planning, implementation, observation and reflection. The students' grades resulted in an average score of 70.4. in the first cycle and increased in the second cycle with an average value of 87.4. The results of this study show that the use of German film media can improve the listening comprehension of the students as well as the positive attitude and activity of the class X students MIPA 5 SMA Negeri 2 Makassar.Keywords: Improvement, German Listening, Media Film Nicos Weg A1